Design of urea granulator with energy optimization - Tan, Chee Fai; Eng, Ling Jong; Wei, Pin Keng; Shaaban, Azizah; Kher, Vee Kiat (2012)
Urea granules are one of the popular fertilizers among synthetic fertilizer industry. Its main function is to provide nitrogen which enhances leaf growth on plant. Urea granules are produced from the process of granulation. Granulation process is divided to wet and dry granulation. Generally, there are two type of dry granulator which is slugger and roller compactor. Roller compactor or also known as roll press is using two counter rotating rolls to compact raw material such as powder to become ribbons or granules. If ribbons instead of granules arc produced from compaction, milling will be used to produce granules. It is difficult obtain a numerical result of the process due to the variety of parameters. Therefore, this work will only consider the parameters which are related to feeder system and roller. The parameters include the feeding rate of feeder, roller force, roller pressure, and roller gap size. While powder flow to roller from feeder, overfeeding may occurs. Overfeeding is harmful because it will cause motor failure. To overcome this problem, the function of roller needs to be improved. The roller will be modified and hence, a new design will be produced.